Application of International Humanitarian Law in Changing Dimensions of Armed Conflict vis-à-vis Cyber Warfare - Pandey, Ashutosh (Unity Journal, 2025)
Transcending the traditional methods of warfare, which were fought on land, sea, and airspace, the dazzling scientific progress of recent decades has given rise to unprecedented means and methods of warfare. The conventional weapons are being replaced by combat robots, drones, cyberweapons, nanotechnologies, and artificial intelligence, among others. While the purpose of the old-school conflicts model was to weaken the opponent’s military power through physical use of force, the modern-day conflicts model, be it international or non-international, deviates in methods of warfare by weakening enemy forces through the use of advanced science and technologies. Cyberwarfare, under IHL, is a relatively new concept that relies on digital infrastructure to conduct hostilities on enemy forces, leading to the triggering of the definition of "attack" under Additional Protocol I and initiating the execution of humanitarian law. While there are numerous complex, unsolved, and unanswered questions, this paper aims to examine the applicability of existing IHL-related legal frameworks and principles to the cyber domain, elucidate the complexities involved in regulating such cyber operations under the purview of IHL, and identify the unique challenges that cyber warfare poses to the application of IHL in this digital realm, especially with regard to the non-kinetic nature of its attacking mechanism. While it is true that states have no common consensus regarding the regulation of war in the cyber domain, the assessment of primary and secondary sources like laws of war, textbooks, journal articles, commentaries, and notable cases ensures that IHL adjusts to the quickly evolving character of contemporary armed conflicts, such as cyber warfare.